Case Report: Two Cases of Pulmonary Artery Dissection in Young Infants - Ren, Chunnian; Zhang, Libing; Yan, Huan; Yang, Zhengbing (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary artery dissection(PAD) is a rare disease. This article reports for the first time the treatment of PAD in young infants. Both cases of infants were treated with surgery. Different surgical methods have achieved different results, which provide ideas for the treatment of pulmonary artery dissection in young infants.